Penerapan Metode Bermain Bowling Aritmatika Untuk Meningkatkan Kemampuan Kognitif Melalui Mengenal Angka 1-20 Pada Anak Kelompok B di TK Kristen Lembon Samala Moronge Selatan 1 - Meiske Ester Tumbel (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to improve cognitive abilities through recognizing numbers 1-20. The method used is the arithmetic bowling method, all children are given the opportunity to play this game. To obtain data in this research the author uses the Class Action Research (CAR) method. This type of research uses the Kemmis and Mc. Taggart quoted Aqip Zainal (2006:31) which consists of 4 stages, namely: 1. Planning, 2. Implementation, 3. Observation, 4. Reflection. In the first cycle of research, it has not yet achieved complete learning, only getting a percentage of 61.1%. And in the second cycle of research, the percentage of children’s achievement increased by 33.3%. So the level of achievement of the percentage of children from cycle I to cycle II increased to 94.4%. In this research, there is still 1 child who has not yet achieved complete learning, so the researcher does remedial action on the child so that he no longer continues in the next cycle of research. Thus, from the results obtained, it means that the purpose of this research has been declared successful. Based on the results of research and discussion, it can be concluded that the method of applying bowling arithmetic through recognizing numbers 1-20 can improve students’ cognitive and learning outcomes. Thus the use of the method of applying arithmetic bowling is proven to be able to improve children’s cognitive abilities through recognizing numbers.